Transcriptome and GWAS analyses reveal candidate gene for seminal root length of maize seedlings under drought stress. (March 2020) - Guo, Jian; Li, Chunhui; Zhang, Xiaoqiong; Li, Yongxiang; Zhang, Dengfeng; Shi, Yunsu; Song, Yanchun; Li, Yu; Yang, Deguang; Wang, Tianyu
Highlights: Seminal roots length contributes to drought tolerance in maize seedlings. Extensive transcriptomic changes in maize seminal root tissues upon drought stress. A combination of transcriptome profiling and GWAS identified important candidate genes related to seminal roots length. Abstract: Water deficits are a major constraint on maize growth and yield, and deep roots are one of the major mechanisms of drought tolerance. In this study, four root and shoot traits were evaluated within an association panel consisting of 209 diverse maize accessions under well-watered (WW) and water-stressed (WS) conditions. A significant positive correlation was observed between seminal root length (SRL) under WS treatment and the drought tolerance index (DI) of maize seedlings. The transcriptome profiles of maize seminal roots were compared between four drought-tolerant lines and four drought-sensitive lines under both water conditions to identify genes associated with the drought stress response. After drought stress, 343 and 177 common differentially expressed genes (DEGs) were identified in the drought-tolerant group and drought-sensitive group, respectively. In parallel, a coexpression network underlying SRL was constructed on the basis of transcriptome data, and 10 hub genes involved in two significant associated modules were identified. Additionally, a genome-wide association study (GWAS) of the SRL revealed 62 loci for the two water treatments. By integrating the results of the GWAS, the common DEGs and the coexpression network analysis, 7 promising candidate genes were prioritized for further research. Together, our results provide a foundation for the enhanced understanding of seminal root changes in response to drought stress in maize.